Multi-temporal Satellite Images Analysis for Assessing and Mapping Deforestation in Um Hataba Forest, South Kordofan, Sudan - Emad H.E. Yasin; Om Habiba Kamil; Budi Mulyana (Journal of Sylva Indonesiana, 2022)
. Sudan is a hot spot for deforestation, despite the increasing awareness of deforestation and its consequences. Consequences are related to increased emissions of greenhouse gases, water pollution, and loss of biodiversity. However, precise information on its forests’ current state is very limited. Therefore, to intervene support of existing resources effectively, it is important to have a better understanding of the process to take place in the country and impact those resources. The objective of this study is assess and map Land use Land cover (LULC) change and analyze the anthropogenic factors causing it in Um Hataba forest, South Kordofan State. The study utilized two-free cloud images (TM 2000 and Sentinel-2 in 2018), field surveys, and questionnaires to analyze the decrease in forest cover. The results indicated there were a decrease in vegetation cover on wadis (clay soil) from 20.98% in 2000 to 15.85% in 2018 and vegetation on sandy soil decreased from 30.29% in 2000 to 30.13% in 2018. While mixed shrubs and grassland increased from 28.60% in 2000 to 33.20% in 2018 of the total area under study and the rainfed agricultural area increased from 20.13% in 2000 to 20.82% in 2018. The main factors of degradation and fragmentation as the expansion of mechanized are rain-fed agriculture, felling of trees and woodcutting, worse grazing activities, and construction of infrastructure. Information garnered from this study can provide a good basis for forest rehabilitation programs and can also be used for developing proper management plans that consider the needs of the communities utilizing the forest.